Patriarchal hegemony of Javanese kings power in Wulang Putri text - Yusro Edy Nugroho; Sahid Teguh Widodo; Wasino; Pardi (Cogent Arts & Humanities)
Colonialism has turned the gender relations in Java into something considerably complex. Through marriage, women were positioned to promote the harmonization of strategic politics of kingdoms. Such a condition results in many studies on several Javanese literary works of Wulang Putri. This research investigates the socio- historical background of the writing of Wulang Putri in the context of the hegemony of Javanese kingdom power. A sociological, literary work in the Gramscian hegemony theory was applied in this study. All data comprised nine literary works of Wulang Putri written in the nineteenth century. The result showed the effect of the literary works in instilling the political influence of the author through a cultural discourse. Such is seen in the post-Java War demilitarization (1825–1830) to maintain the integrity of the kingdom. In addition, there are still traces of efforts to unite the Mataram dynasty through marriages between princes and princesses in four palaces.